UNEXPECTED BEHAVIOUR OF FLUID INCLUSIONS SYNTHESIZED FROM SILVER OXALATE AND AN AQUEOUS NACL SOLUTION - Kruger Y.; Diamond L.W. (My University, 2001)
Fluid inclusions were synthesized in quartz from silver oxalate (Ag2C2O4) and a 6-wt.% NaCl aqueous solution to produce a CO2-H2O-NaCl fluid, following the method of previous workers. Synthesis conditions of 500-650°C and 1500-4500 bar were chosen with the intention of trapping a homogeneous, ternary fluid. The resulting inclusions were analyzed by microthermometry and by Raman spectroscopy. Solid residues in the experimental capsules were analyzed after the syntheses by XRD and SEM-EDS.Several properties of the synthetic inclusions were unexpected: TmCla and Thtot vary over significant ranges and they correlate negatively; the calculated total molar volumes deviate significantly from data on the same bulk composition derived by Gehrig [Gehrig, M., 1980. Phasengleichgewichte und pVT-Daten ternarer Mischungen aus Wasser, Kohlendioxid und Natriumchlorid bis 3 kbar und 500°C. Hochschul Sammlung Naturwissenschaft, Chemie, Band 1. Hochschul Verlag, Freiburg] in an optical cell, and from data derived from our fluid inclusions synthesized for comparison using the gas-loading technique of Frantz et al. [Frantz, J.D., Zhang, Y.-G., Hickmott, D.D., Hoering, T.C., 1989. Hydrothermal reactions involving equilibrium between minerals and mixed volatiles: 1. Techniques for experimentally loading and analyzing gases and their application to synthetic fluid inclusions. Chem. Geol. 76, 57-70]; all fluid inclusions contain a chlorargyrite (AgCl) daughter crystal; and HCO3- was detected in the aqueous phase of the inclusions by Raman spectroscopy, presumably reflecting high concentrations of NaHCO3(aq).All these anomalous features can be traced back to effects caused by precipitation of insoluble AgCl and simultaneous formation of sodium oxalate upon loading the experimental capsules with silver oxalate and NaCl solution. Reconstruction of the chemical reactions that occurred during the hydrothermal syntheses suggests that incomplete redissolution of the AgCl during progressive quartz precipitation and fluid trapping yields inclusions with variable bulk properties. Nevertheless, quite accurate total homogenisation temperatures can be recovered by regressing the Thtot-TmCla correlations, but considerable effort is required.We conclude that silver oxalate should be used in combination with chloride solutions only with extreme caution, whereas the gas-loading technique provides an excellent alternative for the synthesis of CO2-H2O-NaCl fluid inclusions.
Keywords: SYNTHETIC FLUID INCLUSIONS; SILVER OXALATE; GAS-LOADING; CHLORARGYRITE; SYSTEM H2O-CO2-NACL; PVTX PROPERTIES; NAHCOLITE; RAMAN